An automated protocol for performance benchmarking a widefield fluorescence microscope. Issue 11 (13th August 2014) - Halter, Michael; Bier, Elianna; DeRose, Paul C.; Cooksey, Gregory A.; Choquette, Steven J.; Plant, Anne L.; Elliott, John T.
Abstract Widefield fluorescence microscopy is a highly used tool for visually assessing biological samples and for quantifying cell responses. Despite its widespread use in high content analysis and other imaging applications, few published methods exist for evaluating and benchmarking the analytical performance of a microscope. Easy‐to‐use benchmarking methods would facilitate the use of fluorescence imaging as a quantitative analytical tool in research applications, and would aid the determination of instrumental method validation for commercial product development applications. We describe and evaluate an automated method to characterize a fluorescence imaging system's performance by benchmarking the detection threshold, saturation, and linear dynamic range to a reference material. The benchmarking procedure is demonstrated using two different materials as the reference material, uranyl‐ion‐doped glass and Schott 475 GG filter glass. Both are suitable candidate reference materials that are homogeneously fluorescent and highly photostable, and the Schott 475 GG filter glass is currently commercially available. In addition to benchmarking the analytical performance, we also demonstrate that the reference materials provide for accurate day to day intensity calibration. Published 2014 Wiley Periodicals Inc.